The relationship between the sees of Rome, Thessalonica and Constantinople in the context of the development of synodal institutions in the first half of the 5th century - Georgy Zakharov (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2022)
This paper is devoted to the problem of the development of the church organization of the super-provincial level in the Balkan region and to the influence of the Roman and Constantinople Sees on this process. According to the author, the law of emperor Theodosius II, concerning church affairs in Illyricum (421), did not imply the liquidation of the vicariate of Thessalonica created by the Roman see and the transfer of this region to the jurisdiction of Constantinople. It was about endowing the Constantinopolitan see with the function of an alternative judicial instance (along with the see of Thessalonica), which was justified by the status of Constantinople as the New Rome. The protest of Pope Boniface I and the western emperor Honorius against this decision, apparently, led to the fact that the status quo remained in Illyricum. Nevertheless, this law was included in the Code of Theodosius. It is also possible that, along with the diocese of the Orient, Illyricum was meant as the sphere of implementation of the 9th and 17th canons of the Council of Chalcedon (451), which prescribe, in the case of litigation with the participation of the metropolitan, to apply for a trial to the exarch of the diocese or to the Constantinopolitan see. This rule, apparently, was associated with the existence in Constantinople of a "permanent synod", the organization of which did not require significant costs and efforts, in contrast to the synods of dioceses.